PENGARUH WORKING CAPITAL TO TOTAL ASSET, CURRENT LIABILITY TO INVENTORY, OPERATING INCOME TO TOTAL LIABILITIES, & GROSS PROFIT MARGIN TERHADAP PERTUMBUHAN LABA (Studi Pada Perusahaan Manufaktur Food and Beverage Terdaftar Di Bursa Efek Indonesia Periode 2013-2016) - Distha Anggrainingrum; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT The purpose of this study was to analyze the effect of Working Capital to Total Assets (WCTA), Current Liability to Inventory (CLI), Operating Income to Total Liabilities (OITL), and Gross Profit Margin (GPM) on earnings growth. Data obtained by using purposive sampling method with the criteria of manufacturing companies listed on the Indonesia Stock Exchange (IDX) and consistently existed during the study period (2013 to 2016)The results of the analysis show that the data used in this study have met the classical assumptions, which include: no multicollinearity, no autocorrelation, no  heteroscedasticity, and data distributed normally. Data analysis techniques in this study used regression analysis. The four variables used in this study (WCTA, CLI, OITL, and GPM) together had an effect on earnings growth. The predictive ability of the four variables simultaneously is 27.3%. Keywords: Working Capital to Total Assets (WCTA), Current Liability to Inventory (CLI), Operating Income to Total Liabilities (OITL), and Gross Profit Margin (GPM) and profit growth.